2013
DOI: 10.1127/0340-269x/2013/0043-0545
|View full text |Cite
|
Sign up to set email alerts
|

Wetland vegetation of the class Phragmito-Magno-Caricetea in centralItaly

Abstract: A survey and a formalized phytosociological classifi cation of the marsh vegetation of the class Phragmito-Magno-Caricetea in central Italy is presented. Formal defi nitions of the majority of wetland associations recorded from the Italian territory were defi ned using the Cocktail method and applied to a large data set of vegetation plots extracted from the database VegItaly (hosted by the web database system "anArchive"). A total of 43 associations belonging to seven alliances and four orders were recognized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
71
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(81 citation statements)
references
References 38 publications
(60 reference statements)
6
71
0
4
Order By: Relevance
“…In the research area, it has been identified in shallow muddy edges of the water bodies of the Porsuk Dam environs, near Kızılinler, Kıranharmanı, and Sazak Station, between 692 and 833 m. In the study area, many species were found to cooccur with Typhetum latifoliae, but none constantly. Similar Typha latifolia-dominated stands have been recorded in the Lower Volga Valley (Golub et al, 1991), the Marmara Region and Turkey in general Leblebici, 1996, 1997), and across Europe and the Mediterranean (e.g., Minot et al, 2000;Hanáková and Duchoslav, 2002;Otáhelóvá, 2005;Stančić, 2007Stančić, , 2010Bonanno and Lo Giudice, 2009;Lastrucci et al, 2010;Hrivnák et al, 2011;Lastrucci et al, 2012;Landucci et al, 2013).…”
Section: Typhetum Latifoliaementioning
confidence: 85%
See 3 more Smart Citations
“…In the research area, it has been identified in shallow muddy edges of the water bodies of the Porsuk Dam environs, near Kızılinler, Kıranharmanı, and Sazak Station, between 692 and 833 m. In the study area, many species were found to cooccur with Typhetum latifoliae, but none constantly. Similar Typha latifolia-dominated stands have been recorded in the Lower Volga Valley (Golub et al, 1991), the Marmara Region and Turkey in general Leblebici, 1996, 1997), and across Europe and the Mediterranean (e.g., Minot et al, 2000;Hanáková and Duchoslav, 2002;Otáhelóvá, 2005;Stančić, 2007Stančić, , 2010Bonanno and Lo Giudice, 2009;Lastrucci et al, 2010;Hrivnák et al, 2011;Lastrucci et al, 2012;Landucci et al, 2013).…”
Section: Typhetum Latifoliaementioning
confidence: 85%
“…While this appears to be the first record of the association in Turkey, it is by no means rare in southern Europe according to the literature (Jasprica et al, 2003;Stančić, 2007;Bonanno and Lo Giudice, 2009;Lastrucci et al, 2010Lastrucci et al, , 2012Landucci et al, 2013). Most authors assigned Cyperetum longi to the Magnocaricetalia sedge bed vegetation of Phragmito-Magnocaricetea.…”
Section: Cyperetum Longimentioning
confidence: 99%
See 2 more Smart Citations
“…Pri tome su koordinate svih polja pridružene koordinatama fitocenološkog snimka koji je najbogatiji vrstama, u WGS 1984 koordinatnom sistemu. U prikazu istraživanih lokaliteta (Tabela 1) geografske koordinate i naziv glacijalnog jezera prate i preliminarni nazivi zabilježenih fitocenoza na nivou asocijacije ili sveze, čija je nomenklatura usklađena prema više izvora (Horvat et al, 1974;Lakušić et al, 1978;Martinčić, 1994;Školek, 2003;Landucci et al, 2013;Mucina et al, 2016). Fitocenoze su poredane tako da prate gradijent vlažnosti, od akvatičnih submerznih, preko emerznih do vlažnih terestričnih, čime se dobija uvid u zoniranje vegetacije okoline pojedinih jezera (Tabela 1).…”
unclassified